Respuesta :
I don't see any equation. However this equation can b written as follows
7x²=9+x
7x² - x - 9 = 0
7x²=9+x
7x² - x - 9 = 0
so first you need to get into form
0=ax²+bx+c
it is prefered that a is positive
so
7x²=9+x
minus (9+x) from both sides
7x²-1x-9=0
a=7
b=-1
c=-9
for 0=ax²+bx+c
[tex]x=\frac{-b+/-\sqrt{b^2-4ac}}{2a}[/tex]
so, a=7
b=-1
c=-9
[tex]x=\frac{-(-1)+/-\sqrt{(-1)^2-4(7)(-9)}}{2(7)}[/tex] would be the eqquation
but if you did want to solve
[tex]x=\frac{1+/-\sqrt{253}}{14}[/tex]
0=ax²+bx+c
it is prefered that a is positive
so
7x²=9+x
minus (9+x) from both sides
7x²-1x-9=0
a=7
b=-1
c=-9
for 0=ax²+bx+c
[tex]x=\frac{-b+/-\sqrt{b^2-4ac}}{2a}[/tex]
so, a=7
b=-1
c=-9
[tex]x=\frac{-(-1)+/-\sqrt{(-1)^2-4(7)(-9)}}{2(7)}[/tex] would be the eqquation
but if you did want to solve
[tex]x=\frac{1+/-\sqrt{253}}{14}[/tex]